Effect of basalt fiber content on the dynamic tensile properties of rock-filled concrete: Insights from split-hopkinson tensile bar and split-hopkinson pressure bar Brazilian testing - Muhammad Ibrar Ihteshaam; Yixuan Jin; Feng Jin (Results in Engineering)
Rock-Filled Concrete (RFC) is gaining popularity in civil engineering due to its cost-effectiveness and sustainability. While RFC offers numerous advantages, there is limited knowledge available regarding its tensile strength and behavior under dynamic loading conditions, such as impact or seismic events. The scientific literature on the dynamic tensile properties of RFC, especially under high strain rates, remains insufficient. To address this gap, this study investigates the dynamic tensile behavior of basalt fiber-reinforced RFC, focusing on the influence of basalt fiber content on improving its mechanical properties under dynamic loading conditions. Cylindrical specimens (Ø100 × 100 mm) of C15 RFC with basalt fiber contents ranging from 0 % to 3 % by volume were tested using the Split Hopkinson Tension Bar (SHTB) and Split Hopkinson Pressure Bar (SHPB) Brazilian test. Fragmentation analysis and Dynamic Increase Factor (DIF) calculations were conducted to assess crack resistance, ductility, and strain rate sensitivity. Results show that basalt fibers significantly enhance tensile strength and energy absorption, with 2 % fiber content yielding the best performance. At 3 %, fiber agglomeration reduces effectiveness. Fragmentation patterns confirm larger fragment sizes with increasing fiber dosage up to 2 %, indicating improved crack resistance and post-peak behavior. The DIF values align well with the fib Model Code (2010), validating its applicability for RFC under dynamic loading. Both experimental methods produced consistent results, demonstrating that fiber reinforcement delays brittle fracture and improves failure control. This study contributes novel experimental evidence to the field, supporting the use of 2 % basalt fiber content as an optimal reinforcement strategy for RFC in dynamic environments. These findings advance the understanding of RFC's behavior under dynamic loading and provide valuable insights for structural design in seismic-prone or impact-loaded applications.